2022
DOI: 10.1093/nar/gkac296
|View full text |Cite
|
Sign up to set email alerts
|

Human activation-induced deaminase lacks strong replicative strand bias or preference for cytosines in hairpin loops

Abstract: Activation-induced deaminase (AID) is a DNA-cytosine deaminase that mediates maturation of antibodies through somatic hypermutation and class-switch recombination. While it causes mutations in immunoglobulin heavy and light chain genes and strand breaks in the switch regions of the immunoglobulin heavy chain gene, it largely avoids causing such damage in the rest of the genome. To help understand targeting by human AID, we expressed it in repair-deficient Escherichia coli and mapped the created uracils in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…The same authors also reported transcriptional asymmetry of APOBEC3 mutation signatures, a feature we do not observe in hMPXV1 genes. However, both the association with transcription levels and transcription asymmetry are still controversial findings in human cancer genomes ( 10 12 , 36 , 37 ). Thus, experimental analyses will be required to determine the molecular mechanisms of APOBEC3-mediated editing of hMPXV1 genomes and the role of transcription.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors also reported transcriptional asymmetry of APOBEC3 mutation signatures, a feature we do not observe in hMPXV1 genes. However, both the association with transcription levels and transcription asymmetry are still controversial findings in human cancer genomes ( 10 12 , 36 , 37 ). Thus, experimental analyses will be required to determine the molecular mechanisms of APOBEC3-mediated editing of hMPXV1 genomes and the role of transcription.…”
Section: Discussionmentioning
confidence: 99%
“…1B ). The tendency of AID/APOBEC enzymes of preferentially deaminating cytosines near TSS and within tRNA genes in E. coli , yeast and human tumors has been noted previously 44 , 46 , 49 , 50 .
Fig.
…”
Section: Resultsmentioning
confidence: 78%
“…This analysis confirmed that A3A targets hairpin loops 46 and further showed that cytosines in VpC dinucleotides (V is A, C or G) are much better targets for A3A when they appear in hairpin loops than in linear DNA 41 . UPD-seq also showed that AID lacks a strong preference for LGST in replication forks and does not prefer cytosines in hairpins 44 . Normal B lymphocytes undergoing somatic hypermutation and class-switch recombination express AID during the G1 phase of the cell cycle 47 , and hence these results were interpreted to mean that ssDNA in replication forks is effectively protected by RPA from the action of any AID that may leak into the S phase 44 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations